EFFECT OF EFFECTIVENESS OF COLLECTION OF COSTS OF OBTAINING RIGHTS TO LAND AND BUILDINGS (BPHTB) ON INCOME ORIGINAL AREA IN WEST ACEH DAYA DISTRICT - Adiman, Sumardi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
The purpose of this study was to determine the effect of the effectiveness of BPHTB collection on local revenue. This type of research is a causal research that looks for causal relationships. The number of observations in this study were 36 analysis units with 9 sub-districts in the Southwest Aceh district that published BPHTB and PAD reports using the Cross Section for time series data for 4 semesters (2018-2020). The data were processed using regression analysis. The results showed that the effectiveness of BPHTB collection had a significant positive effect on local revenue